The brain-computer analogy—“A special issue” - Matassi, Giorgio; Martinez, Pedro (Frontiers in Ecology and Evolution, 2023)
In this review essay, we give a detailed synopsis of the twelve contributions which are collected in a Special Issue in Frontiers Ecology and Evolution, based on the research topic "Current Thoughts on the Brain-Computer Analogy - All Metaphors Are Wrong, But Some Are Useful". The synopsis is complemented by a graphical summary, a matrix which links articles to selected concepts. As first identified by Turing (1950), all authors in this Special Issue recognize semantics as a crucial concern in the brain-computer analogy debate, and consequently address a number of such issues. What is missing, we believe, is the distinction between metaphor and analogy, which we reevaluate, describe in some detail, and offer a definition for the latter. To enrich the debate, we also deem necessary to develop on the evolutionary theories of the brain, of which we provide an overview. This article closes with thoughts on creativity in Science, for we concur with the stance that metaphors and analogies, and their aesthetic impact, are essential to the creative process, be it in Sciences as well as in Arts.